REMOTE WARFARE AND FRAGILE ACCOUNTABILITY: ETHICAL AND LEGAL CHALLENGES IN NIGERIA’S DRONE COUNTERTERRORISM OPERATIONS - P. Nwosu, Chiedozie; Ngozi Ikpolo, Gabriel; Anselem Onyekachi, Okolie; Joesph Nwambeke, Nwankwegu; Chidiebere Onwe, Daniel (African Journal of Social and Behavioural Sciences, 2026)
In recent times, global counterterrorism efforts and strategies have been reshaped by drones, also known as Unmanned Aerial Vehicles (UAVs). The security architecture of Nigeria has witnessed a significant shift owing to the deployment and use of drones in the present fight against Boko Haram insurgents. Understandably, the use of drones reduces risks associated with military personnel, accentuates precision strikes and enhances surveillance; their usage, however, is associated with some complex ethical concerns. This paper critically examines the ethical concerns surrounding Nigeria’s drone usage and operations, focusing on accountability and transparency, civilian protection and adherence to International Humanitarian Law (IHL); and the broader implications of remote warfare for state legitimacy. The research design of this study is a qualitative, doctrinal, and normative research design, and the theoretical base is anchored on the Just War Theory, International Humanitarian Law, and Moral Responsibility in Human–AI Drone Warfare. The study examines operational and normative challenges associated with drone warfare and concludes that, despite the tactical advantages of Nigeria’s drone programme, it is imbued with intelligence limitations, a lack of adequate regulations and ineffective accountability mechanisms. The paper recommends clearer legal frameworks, institutional restructuring and more transparency, which suggests that institutional reforms, clearer legal frameworks, and greater transparency are vital towards ensuring that drone deployment aligns with International Humanitarian Law, global normative standards and offers adequate protection to civilian populations.